Presentation techniques - Powell, Dick. ([S.l.] : Little, Brown & Company, 1990)
The importance of presenting design ideas with the maximum clarity and precision is the central theme of this manual, which describes the principles of perspective drawing and colouring techniques, with chapters on marker, airbrush and coloured paper rendering and special finishes. All types of line and descriptive drawing are explored, including cutaways and exploded views; and step-by-step drawings show how to build up a product visual, following the entire sequence to the finished drawings. Illustrated throughout with more thanj300 colour illustrations, including examples by some of the most interesting and imaginative designers working today, as well as the author's own drawings, Presentation Techniques will give designers confidence in presenting their ideas in the most visually exciting way.